38‐GHz SIW filter based on the stepped‐impedance face‐to‐face E‐shaped DGSs for 5G application. Issue 6 (21st February 2019) - Li, Jian; Huang, Yongjun; Wang, Huiru; Wang, Ping; Wen, Guangjun
Abstract: In this article, a novel defected ground structure (DGS) is proposed and used to integrate in the metallic layer of millimeter‐wave substrate‐integrated waveguide (SIW) to form a 38 GHz high‐performance bandpass filter. The lower stopband and upper stopband of the designed bandpass filter are achieved by the nature cutoff frequency of SIW and the band notching property of the new proposed DGS, respectively. Numerical optimizations and experimental demonstrations are carried out to validate the proposed DGS‐inspired SIW filter, and good agreements between simulated and measured results are obtained. The measured results indicate a 3.2 GHz passband centered at 38.2 GHz, and the simulated results show good out‐of‐band rejection performance. The proposed filter can be widely used in the upcoming 5G communications.